Anti-diabetic activities of Hibiscus cannabinus extracts leaves and roots in vitro study - M. K., Zuraida; A., Zalinah; Hamid, Muhajir; I., Maznah (Sarawak Biodiversity Centre, 2008)
Hibiscus cannabinus (Kenaf) is an annual herbaceous crop of the Malvaceae family. This plant is composed of various active components including tannins, saponins, polyphenolic, alkaloid, essential oil and steroid, has long been prescribed in traditional folk medicine in India and Africa. The aqueous leaf extract of this plant has been demonstrated to be haematically active and anti-oxidative. The underlying mechanisms that account for Kenaf pharmacology and active components however remain to be elucidated. This experiment was conducted to identify the active compounds of H.cannabinus extracts which had an anti-diabetic activity. There were yields of Hibiscus cannabinus extract which are 28.33% (80% ethanol leaves extract) and 42.23% (hot water leaves extract), 6.62% (80% ethanol extract) and 11.95% (hot water extract). H.cannabinus extracts enhanced insulin secretion in BRIN BD11 cells higher than Glibenclamide (100uM) except 80% ethanol H. cannabinus leaves extract at concentration 1000 ug/ml.